2015
DOI: 10.1007/s00284-014-0764-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage Induced by Heat Stress Could be Relieved by Nitric Oxide in Trichoderma harzianum LTR-2

Abstract: Trichoderma harzianum is an important commercial biocontrol fungal agent. The temperature has been shown to be an important parameter and strain-specific to the mycelia growth of fungi, but less report makes the known of the mechanisms in T. harzianum. In our study, a 6-h treatment of heat increased the thiobarbituric acid reactive substances (TBARS) and nitric oxide (NO) concentration in mycelia to 212 and 230 % the level of the control, respectively. The exogenous NO donor sodium nitroprusside (150 μM) reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…In Candida albicans, NO is involved in oxidative stress and azoles (31). In Trichoderma harzianum, NO can alleviate oxidative damage (32), and this effect was also demonstrated in P. eryngii var. tuoliensis (16).…”
Section: Discussionmentioning
confidence: 92%
“…In Candida albicans, NO is involved in oxidative stress and azoles (31). In Trichoderma harzianum, NO can alleviate oxidative damage (32), and this effect was also demonstrated in P. eryngii var. tuoliensis (16).…”
Section: Discussionmentioning
confidence: 92%
“…This result is consistent with many previous studies 28 . Yu reported that NO can enhance the activity of NOS and NR to reduce oxidative damage and protect the mycelia of T. harzianum from HS 47 . The mechanism of NO enhancement of the response of G. oregonense to HS has been revealed by RNA-Seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, as a physiological regulator, NO signaling is involved in mediating stomatal closure (Noelia et al, 2015 ; Shi K. et al, 2015 ; Chen et al, 2016 ), pollen tube growth (Wang et al, 2009 ). Also, NO plays an essential role in plant disease resistance (Rasul et al, 2012 ; Kovacs et al, 2015 ) and responses to various abiotic stresses such as cold (Fan et al, 2015 ), heat (Yu et al, 2015 ), salt (Liu W. et al, 2015 ), drought (Shan et al, 2015 ), UV-B (Esringu et al, 2015 ) and heavy metal (Alemayehu et al, 2015 ; Chen et al, 2015 ; Kaur et al, 2015 ). These studies have paved the way to understand the signaling roles of NO which may affect cell metabolism, cellular redox balance and gene expression in plants.…”
Section: Crosstalk Between H 2 O 2 mentioning
confidence: 99%